Penatalaksanaan Holistik Scabies pada Anak Usia 4 Tahun di Puskesmas Panjang melalui Pendekatan Kedokteran Keluarga - Anis Syafa'atul Husna (Jurnal Ilmu Medis Indonesia, 2021)
Scabies is a skin disease caused by the infestation and sensitization of Sarcoptes scabiei var. hominis. Scabies attacks in groups because of transmission that quickly occurs through direct or indirect skin contact. This contact occurs especially when living in the same place of residence. In Indonesia, scabies is a skin disease that can often be found in public health centers. The prevalence of scabies in public health centers throughout Indonesia in 2008 reached 5.6-12.9% and is the third-largest skin disease. Primary health services play an important role in scabies in enforcing the right diagnosis and therapy, preventing the disease and spreading the disease to the community because this disease is easily transmitted, especially in dense settlements. Therefore, the appropriate handling of this case is using a family medicine approach. Patient An. H, 4 years of age, complained of itching between the fingers of both hands, especially at night since 3 days ago. The patient had never previously complained of complaints like this. The patient is worried because the complaint spreads to other parts of the body, spreads to people around him, is ridiculed and shunned by his friends. The patient hopes that the itching will disappear, the disease can be cured quickly, does not recur, and does not spread to other people. Patients previously believed that the complaints that arose were viral or bacterial diseases transmitted by other people. Clinically the patient was diagnosed with scabies (ICD 10 B.86). Internal risks include lack of personal hygiene, lack of knowledge, and curative treatment patterns. External threats include similar complaints in the surrounding environment, low-income family hygiene, adequate socioeconomic, and lack of family knowledge—functional degree 1, which is being able to perform activities such as before being sick without difficulty. Furthermore, holistic management is carried out, namely intervention using poster media. In the evaluation, results were obtained in the form of a better understanding of the disease and behavior changes that impacted the success of therapy.